The Influence of Delay and Item Difficulty in Criminal Justice Systems on Eyewitness Confidence and Accuracy - Wheatcroft, Jacqueline M.; Wagstaff, Graham F.; Manarin, Brian (International Journal of Humanities and Social Science Research, 2015)
There is international concern about the negative effects of delays in Criminal Justice Systems. Problems include the deleterious effects that delay can have on witnesses’ memory accuracy and witnesses’ ability to calibrate their memories accurately. Little empirical work has been conducted on these issues combined with item difficulty and the relationship between accuracy and confidence. This paper investigates these issues. 21 witnesses were interviewed about an observed crime and required to answer lawyerly questions used in cross-examination relating to target items classified as ‘easy’, ‘moderate’ and ‘difficult’, in terms of memorability. Participants were interviewed again, 6 months later. A 6 month delay significantly reduced memory accuracy for all levels of question difficulty. Within-subjects C-A relationships seemed to be relatively unaffected by delay; i.e. they tended to be positive for easy and moderate items, and negative for difficult items. Between-subjects C-A relationships were also positive for both easy and moderate items, but improved after 6 months; whereas C-A relationships for the difficult items remained negative and statistically insignificant following the 6 month delay. Delay can have a profound negative effect on witness accuracy that is not likely to be compensated for by improvements in C-A calibration.